Networking Enforced – Comparing Social Services' Collaborative Rationales across Different Welfare Regimes. (30th June 2016) - Breimo, Janne Paulsen; Turba, Hannu; Firbank, Oscar; Bode, Ingo; Sandvin, Johans Tveit
Abstract: Collaboration and networking are ubiquitous, versatile features of social service provision in most Western countries. However, it is an open question whether networking means and entails the same across countries. Comparing regulatory frameworks in three jurisdictions representing distinctive ' worlds of welfare services ' – Germany, Norway and Quebec – this article aims at eliciting the normative rationales that underpin and inform local service networks in child welfare and protection ( CWP ) systems. In Norway, where services are little diversified and largely insular, networking appears as a way of opening up for greater organizational plurality, within and beyond the public sector realm. In Germany in contrast, where services are highly pluralized and fragmented, networks are seen as an instrument for streamlining complexity. As for Quebec – an intermediate case in some respects – networking is envisioned as a catalyst for aligning two co‐existing service streams and mitigating the child protection – family support divide. Interestingly, in all three places, networking is now being enforced through similar highly formalized, top‐down regulatory provisions, even though the intended directions of change differ markedly. This has implications for CWP policy as well as research on networks at large.